INDIVIDUAL APPROACH TO THE REMEDIATION OF SYSTEMIC SPEECH DISORDERS IN PRE-SCHOOL CHILDREN IN THE CONTEXT OF INDIVIDUAL AND INCLUSIVE EDUCATION (Psychology Travelogs, 2025)
The article presents an expanded theoretical and methodological rationale for an individualized approach to the remediation of systemic speech disorders in preschool children within individual and inclusive education. Systemic speech disorders are conceptualized as complex developmental disruptions affecting phonological processing, lexico-semantic structuring, grammatical organization, and pragmatic functioning, which collectively determine a child’s ability to participate in communication and learning activities [1; 4; 5]. Ukrainian research traditions (Kabelnikova, Martynenko, Tyshchenko, Koval) are compared with international frameworks, including Developmental Language Disorder (DLD), the ASHA guidelines, the CATALISE Delphi consensus, as well as the diagnostic standards of ICD-11 and the ICF [5; 7-12].It is argued that traditional speech-therapy practices focused on isolated linguistic components—articulation training, vocabulary memorization, or grammatical drill—do not ensure functional generalization of skills in authentic communicative contexts. Instead, remediation must rely on activity-based integration, communicative agency, individualized developmental planning, and the principles of Universal Design for Learning, which make educational environments accessible to children with diverse linguistic needs [3; 9-10]. The effectiveness of multidisciplinary collaboration involving speech-language therapists, educators, psychologists, and families is emphasized as a key precondition for stable communicative progress.Special attention is devoted to the corrective potential of logorhythmics, narrative practices, role-play, and augmentative and alternative communication (AAC). These methods support sensory-motor integration, increase communicative initiative, and facilitate the transfer of linguistic skills into real interaction with peers and adults [2; 9-10]. The findings demonstrate that an individualized, participation-oriented, and ecologically valid remediation model significantly enhances the speech and communicative development of preschool children with systemic speech disorders. The results outline promising perspectives for implementing comprehensive individualized support frameworks in inclusive early-childhood education settings [1; 3; 10; 12].
Keywords: systemic speech disorders; preschool education; developmental language disorder; individualized approach; speech therapy; inclusive education; individualized development program